Spousal and living related kidney transplantation: Our center experience - Özgen, Utku; Özban, Murat; Birsen, Onur; Yılmaz, Sevda; Dursun, Belda; Ceri, Mevlut; Eker, Mesut; Aydın, Hüseyin Çağatay (BMC, 2021)
Background Kidney transplantation is the most preferred type of renal displacement therapy for end stage renal disease (ESRD) patients. More patients developed ESRD. The most important source is the donations from unrelated spouses. In this study, we aimed to compare the transplantation data obtained from the spouses of the patients with the transplantation data obtained from other relatives. Methods The data including 167 living kidney transplantations performed between January 2006 and December 2019 were retrospectively collected. The patients were divided into two groups; spousal donor group (n: 53) and living-related donor group (n: 114). Results There was no significant difference in delayed graft function in both groups. There were no patients with acute rejection proven by biopsy or considered biochemically in the spousal donor group. With regard to 3-year results in the living-related donor group the patient survival rate was 100%, while it was 98.2% in terms of graft survival. Conclusions In conclusion, similar patient and graft survival rates between spousal donor kidney transplantation and living-related kidney transplantation has made spousal donor kidney transplantation, with possible problems in terms of tissue compatibility, an acceptable alternative to donor supply.
Keywords: Spousal; Living-Related; Kidney Transplantation